Yongdamsagan-tang, a traditional herbal formula, inhibits cell growth through the suppression of proliferation and inflammation in benign prostatic hyperplasia epithelial-1 cells. (14th September 2017) - Park, Eunsook; Lee, Mee-Young; Seo, Chang-Seob; Jeon, Woo-Young; Shin, Hyeun-Kyoo
Abstract: Ethnopharmacological relevance: Benign prostatic hyperplasia (BPH), also called benign enlargement of the prostate, is a progressive disease that is observed in most elderly men. Yongdamsagan-tang, a traditional herbal formula, is used commonly for the treatment of inflammation-related diseases. Although the therapeutic efficacy of Yongdamsagan-tang against BPH in vivo was reported previously, its underlying mechanisms are not clearly understood. Aim of the study: In this study, we investigated the effect of Yongdamsagan-tang water extract (YSTE) and its mechanism on the growth of human BPH epithelial BPH-1 cells. Materials and methods: YSTE was extracted from 11 herbaceous plants and its chemical composition was analyzed by High-performance liquid chromatography (HPLC). YSTE was treated in the epithelial BPH-1 cell line and then cell lysates or supernant were used to evaluate cell viability, cell cycle, proliferation and cytokine production. Results: HPLC revealed that Baicalin and gentiopicroside were involved as the major compounds of YSTE. YSTE treatment in BPH-1 cells repressed cell viability in a dose-dependent manner. Regarding the inhibitory mechanisms of YSTE on cell growth, YSTE inhibited cell proliferation via a decrease in endogenous cyclin D1 protein levels and arrest at the S phase during cell-cycle progression. Furthermore, YSTE treatment in BPH-1 cells suppressed prostaglandin E2 production and cyclooxygenase-2 (COX-2) protein levels. The secretion of the proinflammatory cytokines, interleukin-8 and interleukin-6, was also reduced by YSTE treatment. Conclusions: YSTE in BPH-1 cells showed antiproliferative and anti-inflammatory activities via cell-cycle arrest and downregulation of COX-2 expression, respectively. Taken together, the results of the present study will enhance our understanding of the mechanisms underlying the effect of YSTE in BPH. Graphical abstract: